Rivers of London. Night witch - Cartmel, Andrew; Aaronovitch, Ben, 1964-; Cartmel, Andrew (Titan Comics, a division of Titan Publishing Group, Ltd., 2016)
Press-ganged into helping a Russian oligarch hunt his missing daughter, PC Peter Grant and his boss, Thomas Nightingale, London's only wizarding cops, find themselves caught up in a battle between Russian gunmen, a monstrous forest creature - and their nemesis: The Faceless Man. But as Grant and Nightingale close in on the missing girl, they discover that nothing about this case is what it seems!